2004
DOI: 10.2460/javma.2004.224.380
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risks and benefits of early-age gonadectomy in dogs

Abstract: Because early-age gonadectomy appears to offer more benefits than risks for male dogs, animal shelters can safely gonadectomize male dogs at a young age and veterinary practitioners should consider recommending routine gonadectomy for client-owned male dogs before the traditional age of 6 to 8 months. For female dogs, however, increased urinary incontinence suggests that delaying gonadectomy until at least 3 months of age may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
3
31

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(234 citation statements)
references
References 28 publications
8
192
3
31
Order By: Relevance
“…The risk of post ovariohysterectomy aggression is higher if the bitches had already exhibited aggression before their first birthday or if they were from a predominantly male litter [5,14]. A recent study indicated no difference in aggressiveness between bitches ovariohysterectomized before or after 5.5 months of age [12].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of post ovariohysterectomy aggression is higher if the bitches had already exhibited aggression before their first birthday or if they were from a predominantly male litter [5,14]. A recent study indicated no difference in aggressiveness between bitches ovariohysterectomized before or after 5.5 months of age [12].…”
Section: Discussionmentioning
confidence: 99%
“…A few dogs developed hip dysplasia, but they did not require surgical or prolonged medical management. 3 A similar study 4 for which follow-up monitoring was available for as long as 11 years after gonadectomy revealed a significant increase in the incidence of hip dysplasia among dogs gonadectomized before 5.5 months of age, compared with the incidence for those gonadectomized after 5.5 months of age. However, there was a lower rate for euthanasia among the early-age gonadectomized dogs with hip dysplasia.…”
Section: Orthopedic Diseasesmentioning
confidence: 99%
“…14,15,28,34 The effect of sex hormones on orthopedic disease has also been explored via comparisons between gonadectomy performed at early and traditional ages. 3,4 Comparison of outcomes for shelter dogs gonadectomized before or after 24 weeks of age revealed no association between age at gonadectomy and frequency of musculoskeletal problems during the 4 Small Animals years after gonadectomy. A few dogs developed hip dysplasia, but they did not require surgical or prolonged medical management.…”
Section: Orthopedic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations